UMP receives visit from Sekolah Menengah Imtiaz Yayasan Terengganu Marang - Yong, Ying Mei (UMPSA, 2023)
PEKAN, 8 February 2023 – A delegation of 30 people from Sekolah Menengah Imtiaz Yayasan Terengganu (SMI YT), Marang including the principal, teachers and students visited Universiti Malaysia Pahang (UMP) and Confucius Institute (CI).